The Controversy of Eid al-Adha Sacrificial Slaughter Amid the FMD Outbreak in Indonesia: A Sociology of Religion Perspective - Mubaraq, Zulfi; Abdullah, Irwan; Fatoni, Abdul Wahab; Sutawi; Zalizar, Lily; Kusumastuti, Frida (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2025)
The celebration of Eid al-Adha, traditionally a festive and communal expression of Islamic devotion, became a source of public controversy in Indonesia during the Foot-and-Mouth Disease (FMD) outbreak affecting livestock. At the core of this controversy lies an ethical and theological dilemma: whether sacrificial slaughter should proceed when animal health is compromised. This study explores three main aspects: first, the forms in which the controversy manifested; second, the factors that contributed to public and institutional disagreement; and third, the broader implications for Muslim social and spiritual life. Data were collected from selected online news articles and analyzed using Pan and Kosicki’s framing analysis model, including syntactic, script, thematic, and rhetorical structures. The findings indicate three major forms of controversy: affirmation of slaughter validity, uncertainty due to health risks, and concerns about ritual permissibility. Contributing factors include widespread media coverage, government restrictions, and religious fatwas. The implications range from economic losses in the livestock trade and reduced enthusiasm for sacrifice to social tensions within communities. This study concludes that the FMD outbreak disrupted not only ritual practice but also the socioreligious harmony surrounding Eid al-Adha, revealing tensions between religious commitment, health concerns, and public discourse.